Impelementasi Model Waterfall pada Media Pembelajaran Pengenalan Angka dan Huruf Berbasis Android - Sidik Sidik; Muhammad Fajar Syahroni (JURNAL TEKNIK KOMPUTER, 2019)
The era of globalization, information technology is advancing rapidly, one of which is the development of interactive animation. Interactive animation technology is now widely used in various industries, such as advertising, education, tourism, entertainment, and so on. In the world of education, interactive animation can be applied as an effective learning medium. In the preparation of this study, the authors used the Waterfall model to design the system and to design learning media using Adobe Flash Professional CS6 which is considered very suitable in making interactive animation-based learning media. The Waterfall Model, is the most familiar system model and is widely used in designing interactive animation-based applications. In making interactive animation-based learning media can increase learning interest and students' attention to the introduction of numbers and letters and kinds of sounds and images. In addition, students can also learn while playing and train to recognize numbers and letters, with varied images. Respondents in this study consisted of teachers and students. The results of this study 80% stated that this learning media was easy to use, 90% said that respondents liked the application of media learning to recognize numbers and letters based on interactive animation, 70% of respondents said they learned to recognize numbers and letters that were fun. Besides this interactive animation-based learning media helps train students to recognize numbers and letters, with diverse images, and can also facilitate teachers in training students at school.